The beast must die [videorecording (DVD)] - Jumbo, Cush; Howle, Billy, 1989-; Parker, Nathaniel, 1962-; Dermody, Maeve; McMeekin, Douggie; Tomlinson, Mia; Sayburn, Barney; James, Geraldine, 1950-; Harris, Jared, 1961-; Blake, Nicholas, 1904-1972 (AMC Studios, 2022)
Following the death of her son in a hit and run, all Frances Cairnes wants is to hunt down and kill the man she believes is responsible. When she finally tracks him down, she tricks her way into his house and plots his murder from within.